The Impact of Green Knowledge on Public Interest in Eco-Friendly Gold Management Services: The Mediating Role of Attitude - Faris, Muhammad; Wulandari, Ririn (Dinasti Publisher, 2025)
This study investigates the impact of green knowledge on public interest in environmentally friendly gold mining services, with a particular focus on the mediating role of attitudes. Despite widespread concerns about the environmental and health risks associated with mercury use in small-scale gold mining, traditional practices continue to be prevalent due to various socio-economic factors. Using a quantitative approach, data were collected from 143 small-scale gold miners in Situbabakan Village, Lebak Regency, Banten Province, through a structured questionnaire. The study employed Partial Least Squares Structural Equation Modeling (PLS-SEM) to analyze the relationships between green knowledge, attitudes, and purchase intentions. The findings reveal that while green knowledge alone does not significantly influence the purchase intention of gold mining services, it positively affects the attitudes of miners towards environmentally friendly practices. Moreover, the study demonstrates that attitudes significantly mediate the relationship between green knowledge and purchase intention, highlighting the crucial role of psychological factors in promoting sustainable behavior. These results underscore the need for targeted educational interventions that not only increase environmental awareness but also foster positive attitudes toward sustainability. The study concludes that enhancing green knowledge and attitudes could play a vital role in encouraging the adoption of eco-friendly gold mining practices